2018
DOI: 10.24818/rmci.2018.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Positive Autism: Investigation of Workplace Characteristics Leading to a Strengths-Based Approach to Employment of People with Autism

Abstract: United Nations declares that employment is a basic human right. Numerous public policies reference the devastating impact of unemployment on health and social inclusion and seek to promote the economic participation of people with disabilities. Some researchers reckon high levels of economic marginalisation are experienced by people with a disability in Australia, in comparison with other OECD countries.In the literature, 80% unemployment rates are reported among working-age people with autism spectrum disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Under these types of conditions, the visual and spatial thinking capabilities stemming from neurodiversity may be particularly advantageous. Consistent with research findings that show that neurodiversity can lead to creativity and the generation of novel solutions to problems (Wong et al, 2018), novel problem situations may reinforce the link between the information processing competencies associated with neurodiversity and leadership behavior, as they may provide an opportunity for those cognitive strengths to manifest.…”
Section: A Model Of Neurodiverse Leadershipsupporting
confidence: 78%
See 3 more Smart Citations
“…Under these types of conditions, the visual and spatial thinking capabilities stemming from neurodiversity may be particularly advantageous. Consistent with research findings that show that neurodiversity can lead to creativity and the generation of novel solutions to problems (Wong et al, 2018), novel problem situations may reinforce the link between the information processing competencies associated with neurodiversity and leadership behavior, as they may provide an opportunity for those cognitive strengths to manifest.…”
Section: A Model Of Neurodiverse Leadershipsupporting
confidence: 78%
“…Accordingly, neurodiverse individuals are more likely to engage in spatial thinking than neurotypical, language-based thinkers (Grandin, 2009). Given the uniqueness of such visual processing, research has shown that neurodiversity can lead to creativity and the generation of novel solutions to problems (Wong, Donelly, Neck, & Boyd, 2018). Interestingly, the findings of studies examining the cost and benefits of hiring employees with ASD suggest that the addition of such diverse processing skills and approaches also helps to create more adaptive work environments (see Scott et al, 2017).…”
Section: Neurodiversity As a Leadership Capabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an important consideration in whether people's psychological characteristics change is if they want to change (Hudson et al, 2021;Hudson & Roberts, 2014). It is entirely possible that, in identifying as someone either with ASD or BAP traits, people may come to recognize the strengths of these characteristics and identity and ultimately resist contexts that might modify these traits (Caspi et al, 2005;Large & Serrano, 2018;Niemiec et al, 2017;Wong et al, 2018). Among those who do want to change, there have been positive examples of interventions that have proven effective at changing broader personality traits among younger adults.…”
Section: Discussionmentioning
confidence: 99%